Impact of Giving Monosodium Glutamate on Health - Melia Munasiah (Global Health Science Group, 2020)
Monosodium glutamate or MSG is a food additive that is widely used in various countries to add flavor to the food to be served. If MSG is consumed by someone who cannot tolerate the amount of more than 3g / day, it will cause detrimental effects on health. Symptoms of the complex syndrome include: burning sensation in the back of the neck spreading to the arms and chest, numbness in the back of the neck, facial stiffness, chest pain, nausea, and drowsiness. The writing of this article uses a review article study. The source of the literature used in compiling this literature uses manuals and recent studies obtained through the process of literature searching related to the relationship of MSG to health. The publication year of the articles used is between 2000-2018 from several sources obtained. Based on a review of the scientific evidence that has been conducted on the safety of MSG, it is concluded that there is no scientific evidence that the addition of MSG in food in the long term causes nerve cell damage.